Kinetic investigations of Cl atom initiated photo-oxidation reactions of cyclic unsaturated hydrocarbons in the gas phase: an experimental and theoretical study. (3rd July 2017) - Vijayakumar, S.; Ramya, C. B.; Kumar, Avinash; Rajakumar, B.
Abstract : Cl atom initiated photo oxidation kinetics of cyclohexene and cycloheptene. Abstract : Temperature dependent rate coefficients for the reactions of Cl atoms with cyclohexene and cycloheptene were measured over the 280–360 K temperature range using a relative rate experimental technique with reference to 1, 3-butadiene and isoprene. To complement the experimental results, computational calculations were performed in combination with canonical variational transition state theory (CVT) with small curvature tunneling (SCT) and conventional transition state theory (CTST) coupled with Wigner's and Eckart's symmetric and unsymmetric corrections at the MP2/6-31G(d, p) level of theory. The measured rate coefficients for the reactions of Cl atoms with cyclohexene and cycloheptene are k R1298K = (3.26 ± 0.35) × 10 −10 cm 3 molecule −1 s −1 and k R2298K = (5.68 ± 0.9) × 10 −10 cm 3 molecule −1 s −1 respectively. The temperature dependent Arrhenius expressions are found to be k R1280–360K = (5.53 ± 1.84) × 10 −11  exp[(516 ± 104)/ T ] cm 3 molecule −1 s −1 and k R2280–360 K = (3.42 ± 2.9) × 10 −11  exp[(827 ± 268)/ T ] cm 3 molecule −1 s −1 for cyclohexene and cycloheptene respectively. The Cl atom addition reactions are more favorable in the case of cyclohexene, whereas in the case of cycloheptene both addition and abstraction channels are favorable. The rate coefficients for the reactions of cyclohexene and cycloheptene with Cl atoms are compared with the rate coefficients of OH and NO3 radicals, and O3 molecules to know the significance of the Cl atom reactions in the Earth's atmosphere. The cumulative lifetimes, reaction mechanism, feasibility of the reaction and other atmospheric implications of the test molecules were discussed.